EFFECTS OF ALIEN WEEDS ON PHOTOSYNTHETIC EFFICIENCY OF GREEN GRAM AND MUSTARD - Ghayal, Nivedita Amarendra; Hase, C. P. (Current Botany, 2018)
The allelopathic potential of leachates, extracts, decomposed residues depends upon the type and quantity of allelochemicals existing in them. The allelopathic stimulation or inhibition in recipient plants and their response also depends on the way they are exposed to the allelochemicals. The allelopathic impact of leachates and extracts (foliar application) and residue (soil application) was analyzed on the test-crop. The results clearly indicated the inhibitory nature of the treatments at higher concentrations on mungbean and mustard. The changed manifestations recorded in treated plants at different levels are usually through the alterations in very important physiological process in the plant body like photosynthesis. It was observed by the change in the contents of different chlorophyll pigments, which ultimately must have affected the process of photosynthesis. The results indicated that at higher concentration treatments there was considerable reduction in both the test crops.